COMPARISON THE REAL COST WITH INA-CBG’S PACKAGE TARIFF AND ANALYSIS ON THE FACTORS INFLUENCING THE REAL COST FOR THALASEMIA INPATIENTS USING JAMKESMAS IN RSUP Dr. SARDJITO YOGYAKARTA - Aditya Maulana Perdana Putra; Fita Rahmawati; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
In 2011, health insurance in patients with thalassemia major help families of patients because thalassemia treatment cost is quite high. In the implementation of INA-CBGs there are some problems, one of which is related to the payment in which difference occurs between tariff of INA-CBGs with real cost.The aim of this research was to find out the extent of the difference between the real tariff and the tariff of INA-CBGs, factors that influence real cost and the description of the appropriateness of therapy towards the Jamkesmas inpatients with Thalassaemia at Sardjito Hospital Yogyakarta.This was an analytical-observational research with of retrospective research design. The object of the research was the files of the inpatient claims and medical records of Jamkesmas patients with Thalassaemia in the period of April 2011 – March 2012 in Sardjito Hospital Yogyakarta. The data analysis was conducted with one sample test to compare between the rate of the real cost and the INACBG’s tariff. Meanwhile, the correlation test and the linear regression test were conducted to find out factors that influence the cost. The result of the research showed that a positive difference between the real cost and the tariff of INA-CBGs was IDR104.498.068 from 138 episodes of care. The average cost of healthcare for Thalassaemia based on the tariff of Sardjito Hospital at the severity level 1 was IDR1.058.823 + 591.923. The three most significant cost components included the blood bag, drugs or medical stuffs and accommodation/hospitalization cost. The result of the correlation test showed that the blood bag, drugs and medical stuffs, hospitalization/accommodation, clinical pathology examination and visite had a strong influence towards the real cost. Meanwhile, from the value of variable coefficients (B), it was known the order of variable that influence the real costs were visite, hospitalization/accommodation, blood bag, drugs and medical stuffs, and clinical pathology examination. From the analysis of the suitability of an indication, there were 5 drugs that are not consistent with the diagnosis of patients and one drug that was not appropriate for the patient.Keywords: INA-CBGs, Thalassaemia, cost, appropriateness of therapy